Isolation of Streptococcus suis using a selective medium. - Rosendal, S (1986)
A selective medium containing tryptic soy agar, 5% defibrinated bovine blood, crystal violet, nalidixic acid and gentamicin significantly improved the isolation rate of Streptococcus suis from tonsilar tissue of slaughtered pigs. Ninety-five percent of the S. suis isolates identified in Guelph were confirmed as S. suis in Copenhagen, but only six out of 21 isolates typed as capsular serotype 2 in Guelph were confirmed to possess serotype 2 antigen in Copenhagen. Sixty-four percent of the S. suis isolates were not typable within the current scheme of capsular serotypes from 1 to 13 and type 1/2.